Identification of the Cold Receptor TRPM8 in the Nasal Mucosa. Issue 4 (July 2015) - Liu, Shao-Cheng; Lu, Hsuan-Hsuan; Cheng, Li-Hsiang; Chu, Yueng-Hsiang; Lee, Fei-Peng; Wu, Chi-Chung; Wang, Hsing-Won
Background: The transient receptor potential channel melastatin 8 (TRPM8) has been proposed to be a cold receptor. However, its distribution and physiologic role in the nose is not yet fully explored. Objective: We investigated the expression of TRPM8 in human nasal mucosa and its function when using the TRPM8 agonist. Methods: Immunohistochemistry was used to study TRPM8 receptors in the nasal mucosa from patients with and those without allergic rhinitis (AR). By using isometric contraction studies, we also tested the effectiveness of the TRPM8 agonist menthol on nasal mucosa. Changes in nasal mucosal contractility in response to the application of the adrenergic agent methoxamine were also measured. We explored the effect of menthol on electrical field stimulation (EFS) induced nasal mucosal contractions. Results: TRPM8 immunoreactivity was present principally in the nasal cilia, epithelium, and subepithelium around the glands. Except for nerve fibers, no obvious TRPM8-immunoreactive cells were detected in connective tissues. The immunoreactivity revealed no significant difference between patients with AR and those without AR. Adding menthol had a negligible effect on the basal tension of the nasal mucosa, but higher doses of menthol had a significant spasmolytic effect on nasal mucosa precontracted with methoxamine. Menthol inhibited the spike contraction induced by EFS, even at low doses. Conclusions: The finding of the TRPM8 immunoreactivity underlines the important physiologic role of the nose in temperature regulation, both in patients with allergy and those without allergy. Isometric contraction studies demonstrate the role of TRPM8 in regulating nasal patency and airway resistance. The antiadrenergic effect of menthol showed an effect apparently opposite that of clinical observations, that we usually feel decongested after menthol inhalation. The underlying mechanisms deserve further investigation, and the TRPM8 antagonists deserve consideration for treatment of rhinitis in a therapeutic trial.